First documented record of a living solemyid bivalve in a pockmark of the Nile Deep-sea Fan (eastern Mediterranean Sea) - Rodrigues, Clara F. (2012)
A living specimen of a solemyid bivalve was collected at bathyal depths near a pockmark in the Nile Deep-sea Fan (eastern Mediterranean) and is here presented. Both taxonomic and molecular results suggest a Solemya species but due to the small size of the animal and the lack of molecular data for other solemyid species the species cannot be determined. This is the first record of a living solemyid from deep-sea cold seeps in the Mediterranean Basin.